Zbirka psihologijskih skala i upitnika: svezak 13 - Šimunić, Ana; Nekić, Marina; Ombla, Jelena; Tokić, Andrea; Vidaković, Marina (2026)
The thirteenth volume of the Collection of Psychological Scales and Questionnaires continues the long-standing tradition of presenting the scientific work of the faculty members of the Department of Psychology at the University of Zadar. It is a unique publication in Croatia that provides various users within the field of psychology with access to measurement instruments. Owing to the diversity of the scales and questionnaires presented, the publication is of interest not only to researchers but also to practitioners working in a variety of sectors, including education, social welfare, healthcare, human resources, and others. It is particularly valuable to psychology students, who may find instruments suitable for their undergraduate or graduate theses, as well as to anyone interested in keeping up with recent psychological research and emerging constructs across different areas of psychology.The content of the thirteenth volume reflects thematic diversity through 14 contributions covering various fields of psychology, including educational psychology, clinical and health psychology, organizational psychology, environmental psychology, and others. The questionnaires and scales are intended to measure constructs in different populations, ranging from children and adolescents to older adults. A total of thirteen faculty members from the Department of Psychology at the University of Zadar contributed to the preparation of this volume. Each contribution includes the theoretical background of the construct, a description of the measurement instrument (including administration and scoring procedures), a presentation of the samples on which the instrument was applied, the psychometric properties of the instrument, and a list of references. At the end of each contribution, the complete measurement instrument, together with instructions for its administration, is provided and made available free of charge.The contributions include both newly developed questionnaires and adaptations of existing measurement instruments from other languages. The instruments are either publicly available for research purposes or have been adapted and published with the permission of the authors of the original scales and questionnaires. Specifically, five contributions present original instruments developed by the authors and their collaborators as part of their broader scientific work and therefore constitute original copyrighted works (Questionnaire of Perceived Quality of Healthcare Services, Student Feedback Scale, New Scale of Emotional and Sexual Infidelity, and Active and Passive Sexting Questionnaire). The remaining ten contributions present adapted versions of existing instruments from other languages, for which the authors obtained permission from the authors of the original versions (Connectedness to Nature Scale, Nature Contact and Nature Noticing Activities List, Parental Regret Scale, Rational and Intuitive Decision-Making Styles Scale, School Psychologists/Professional Associates Stress Inventory, Centrality of Event Scale – Short Form (CES-7), Problematic Mobile Phone Use Scale, Workplace Fear of Missing Out (WFoMO), and Spiritual Health and Life-Orientation Scale). We believe that the contributions included in this thirteenth volume of the Collection of Psychological Scales and Questionnaires will be useful to psychologists in their future research, teaching, and professional activities.